Assessing food acquisition, preparation, and consumption practices in South Asia: A systematic review of assessment tools - Patwardhan, Sharvari; Boncyk, Morgan; Avula, Rasmi; Blake, Christine; Akter, Fahmida; Das, Jai K.; Silva, Renuka; Menon, Purnima; Scott, Samuel P. (2025)
Assessing behaviors related to food choice at individual- and household-levels is essential for improving household diets, but assessment tools are limited. We conducted a systematic review to identify gaps in existing assessment tools for food acquisition, preparation, and household consumption practices in South Asia, wherein diets are rapidly changing, and triple burden of malnutrition is emerging.